SEMIGRUP – Γ YANG DIBANGKITKAN DARI SUATU SEMIGRUP - Sumanto, Y.D (MATEMATIKA, 2015)
Every Element on semigroup   can be regarded as binary operation on . Furthermore every element semigroup  can be defined a binary operation on , if   is set of binary operation that is defined from element semigroup , then  can be formed become semigroup .